2003
DOI: 10.1108/02686900310488258
|View full text |Cite
|
Sign up to set email alerts
|

ISO 9000 implementation: a study of manufacturing companies in Saudi Arabia

Abstract: This study identifies the costs, benefits and the satisfaction level with ISO 9000 implementation in Saudi Arabian firms. A survey of 140 ISO 9000 certified manufacturing companies was carried out. The results suggest that these manufacturing companies were satisfied with ISO 9000 as far as the benefits gained from certification and its costs were concerned. They considered the benefits of ISO 9000 certification to exceed the costs of attaining the standards, and believed that ISO 9000 contributed to organisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Quality is imperative for higher education institutions to achieve competitiveness (Hasan et al 2008 ;Magd et al 2003 ;Yunus et al 2010 ). Education quality is primarily determined on the basis of students' experience being the primary stakeholder of educational institutions (Hill et al 2012 ;ISO 2007 ).…”
Section: Introductionmentioning
confidence: 97%
“…Quality is imperative for higher education institutions to achieve competitiveness (Hasan et al 2008 ;Magd et al 2003 ;Yunus et al 2010 ). Education quality is primarily determined on the basis of students' experience being the primary stakeholder of educational institutions (Hill et al 2012 ;ISO 2007 ).…”
Section: Introductionmentioning
confidence: 97%
“…Since, the issuance of ISO 9000 series in 1987 by the International Organization for Standardization (ISO), the standards have been widely accepted by many organizations across all industries, regardless of their size or products (Magd et al, 2003;Magd, 2006;Naser et al, 2004;Saraiva and Duatre, 2003). Research on the effects of implementing ISO 9000 series has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…Studies and researches that looking for the impact of ISO 9001 certification were started in the last century. Magd et al (2003), Magd (2006) showed a positive impact of ISO 9000 certification in Saudi Arabia organizations which has improved the quality system efficiency, produced a better documentation and increased quality awareness in the Saudi Arabia firms. Chris et al (2007) preformed an event study and found that the time-based efficiency started to improve right after the implementation of the ISO 9000.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Many researchers tried to find the impact of ISO 9001 certification on all types of firms and companies around the world, where certification by ISO 9000 have been increased around the world year by year, for example Magd et al (2003) showed that in 2000 the number of certification are increased from 343 to 643. Studies and researches that looking for the impact of ISO 9001 certification were started in the last century.…”
Section: Literature Reviewmentioning
confidence: 99%